Two Aspects of Activation: Arousal and Subjective Significance – Behavioral and Event-Related Potential Correlates Investigated by Means of a Modified Emotional Stroop Task - Imbir, Kamil; Spustek, Tomasz; Bernatowicz, Gabriela; Duda, Joanna; Żygierewicz, Jarosław (Frontiers in Human Neuroscience, 2017)
The arousal level of words presented in a Stroop task was found to affect their interference on the required naming of the words' color. Based on a dual-processes approach, we propose that there are two aspects to activation: arousal and subjective significance. Arousal is crucial for automatic processing. Subjective significance is specific to controlled processing. Based on this conceptual model, we predicted that arousal would enhance interference in a Stroop task, as attention would be allocated to the meaning of the inhibited word. High subjective significance should have the opposite effect, i.e. it should enhance the controlled and explicit part of Stroop task processing, which is color naming. We found that response latencies were modulated by the interaction between the arousal and subjective significance levels of words. The longest reaction times were observed for highly arousing words of medium subjective significance level in comparison to most of other conditions. Arousal shaped event related potentials in the 150-290 ms time range, while effects of subjective significance were found for 50-150, 150-290 and 290-530 ms time ranges.